Self-blood pressure measurement as compared to office blood pressure measurement in a large Indian population; the India Heart Study. Issue 7 (July 2020) - Kaul, Upendra; Wander, G.S.; Sinha, Nakul; Mohan, Jagdish C.; Kumar, Soumitra; Dani, Sameer; Ponde, Chandrashekhar K.; Pinto, Brian; Dalal, Jamshed; Hiremath, Jagdish; Kapoor, Sunil; Baruah, D.K.; et al.
Abstract : Objective: India Heart Study (IHS) is aimed at investigating the agreement between office blood pressure measurement (OBPM) and self (S)BPM in a hypertension-naive population. Methods: A total of 18 918 individuals (aged 42.6 ± 11.7 years, 62.7% men), visiting 1237 primary care physicians across India, underwent OBPM. They performed SBPM for a period of 1 week using a validated oscillometric BP monitor that was preprogrammed to adhere to a guideline-based SBPM-schedule and blinded to the results. Thereafter, individuals underwent a second OBPM. Available laboratory results were obtained. Thresholds for elevated OBPM and SBPM were 140/90 and 135/85 mmHg, respectively. Results: On the basis of first-visit OBPM and SBPM, there were 5787 (30.6%) individuals with normotension; 5208 (27.5%) with hypertension; 4485 (23.7%) with white-coat hypertension (WCH) and 3438 (18.2%) with masked hypertension. Thus, a diagnosis contradiction between SBPM and first-visit OBPM was seen in 9870 (41.9%) individuals. On the basis of second-visit OBPM, the normotension, hypertension, WCH and masked hypertension prevalence values were 7875 (41.6%); 4857 (25.7%); 2397 (12.7%) and 3789 (20.0%). There was poor agreement (kappa value 0.37) between OBPM of visit 1 and 2 with a diagnosis difference in 6027 (31.8%) individuals. The majority of masked hypertension and WCH individuals had BP values close to thresholds. Conclusion: There was a poor agreement between OBPM of visit1 and visit 2. Likewise, the agreement between OBPM at both visits and SBPM was poor. SBPM being considered to have a better correlation with patient prognosis should be the preferred method for diagnosing hypertension. Abstract : Supplemental Digital Content is available in the text